2016
DOI: 10.1021/acs.orglett.6b02478
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the Total Synthesis of Diverse Bromo-Chamigrenes

Abstract: Several dozen spirocyclic sesquiterpenoids known as the bromo-chamigrenes have been isolated to date. Yet, despite their unique structures, synthetic efforts toward this collection have been modest. Herein, we outline two strategies to generate their skeletons based on (1) a biomimetic bromonium-induced polyene cyclization using BDSB (EtSBr·SbClBr) and (2) a Diels-Alder reaction which ultimately delivered four members of the class. In addition, X-ray crystallography reveals that one member has a structure in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…Very recently, this natural product was also reached by Snyder using a similar oxidative end game. 22 Conversely, 10- epi -dactylone ( 3 ) could be obtained from 9 by an allylic oxidation using SeO 2 , which provided allylic alcohol 22 in moderate yield, followed by further oxidation with an excess of MnO 2 , consistent with the reaction sequence reported by Burns and co-workers. 11 Using this strategy, were able to reach both 2 and 3 in the racemic series from a single precursor, viz.…”
Section: Synthesis Of Dactylone and 10- Epi -Dactysupporting
confidence: 84%
See 1 more Smart Citation
“…Very recently, this natural product was also reached by Snyder using a similar oxidative end game. 22 Conversely, 10- epi -dactylone ( 3 ) could be obtained from 9 by an allylic oxidation using SeO 2 , which provided allylic alcohol 22 in moderate yield, followed by further oxidation with an excess of MnO 2 , consistent with the reaction sequence reported by Burns and co-workers. 11 Using this strategy, were able to reach both 2 and 3 in the racemic series from a single precursor, viz.…”
Section: Synthesis Of Dactylone and 10- Epi -Dactysupporting
confidence: 84%
“…Remarkably, the Burns and Snyder group disclosed their total syntheses 9 using the same strategy almost simultaneously. 11 , 22 The synthesis of halogenated chamigranes remains a significant challenge due to the difficulty in forging sterically encumbered spirocyclic quaternary centers and 2° neopentyl bromides. 23 26 We envisioned that the synthesis of the spiroundecane 10 could be achieved through a Diels–Alder reaction between exocyclic enone 11 and isoprene, followed by a late stage bromination ( Figure 6 ).…”
Section: Synthesis Of Dactylone and 10- Epi -Dactymentioning
confidence: 99%
“…Critically, we observed no a-bromination of the aldehyde within 23, though such reactions have been observed in other contexts. 15 As further evidence for the uniqueness of the developed solution and the power of BDSB to effect this cyclization/ring-expansion chemistry, attempts to use NBS in HFIP, convenient and readily executed conditions recently reported to effect bromeniuminduced polyene cyclizations with equal facility as BDSB, 16 did Scheme 3 Total synthesis of laurendecumallene B (7): (a) allyl acetate (10.0 equiv. ), Grubbs 2 nd generation initiator (3 mol%), 25 C, 4 h, 54%, 76% brsm; (b) NaHCO 3 (6.0 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…There was only one synthetic study toward 1 until two elegant total syntheses were reported very recently by the groups of Trauner and Burns, in addition to a formal synthesis by Snyder et al Burns and co‐workers tested and realized the aforementioned photocycloaddition under UV irradiation ( λ =350 nm). Later Trauner et al.…”
Section: Figurementioning
confidence: 99%
“…There was only one synthetic study [3] toward 1 until two elegant total syntheses were reported very recently by the groups of Tr auner [4] and Burns, [5] in addition to af ormal synthesis by Snyder et al [6] Burns and co-workers tested and realized the aforementioned photocycloaddition under UV irradiation (l = 350 nm). Later Tr auner et al also independently reported their interesting findings in photochemical relationships among brominated sesquiterpenes from Aplysia dactylomela.…”
mentioning
confidence: 99%